Desenvolvimento de negócio de locação e venda de andaimes com base na excelência operacional - Gomes, Rogério Conceição (2020)
This report presents the development of a scaffolding rental and sale business to take advantage of the opportunity identified in the civil construction market, by the Brazilian subsidiary of the German multinational company Layher. It was motivated by the verification of competitors 'failure to meet their customers' requirements. The branch office is located in the municipality of Cajamar, state of São Paulo and operates nationwide through offices in Porto Alegre (RS), Duque de Caxias (RJ) and Eusébio (CE). The work started based on an operational excellence program, which has been underway at the company since 2018, which was continued, expanded and enriched, with the work reported here. After less than two years of development, some concrete results were obtained. Of the indicators for assessing the evolution of work, 33% had their goals achieved and the remaining 66% were dependent on adjustments caused by the COVID – 19 crisis. As for innovation, considerable changes were made in the analysis of in-formation from customers, such as the validation of some hypotheses raised to assist decision making by senior management. This became relevant in the preparation of the company's stra-tegic plan. Another relevant innovation was the integration of two working methods, that of operational excellence and that of solving problems and taking advantage of opportunities. The resulting impacts created value for senior management, even if still partial, with greater engage-ment and involvement of key employees in obtaining the results defined for the business. The most relevant ones were obtained in meeting customer requirements, such as the reduction in complaints that fell from 3% to 0.8% in less than a year, before the pandemic crisis. The com-plexity in the development of the work was due to some factors, among them, the scarcity of data on the performance of the company's operating segment, due to the dispersion of large, medium and small companies, across all regions of Brazil, with very low participation in asso-ciations in the civil construction sector. The survey on customer satisfaction also required a lot of effort from the managers of the company's offices in São Paulo and other states, due to dif-ficulties in accessing customers for interviews. However, the most complex part of the devel-opment of this work, was the integration of the concepts and activities that were already being carried out within the operational excellence program developed by Atoth Consulting, which was underway, with the problem solving and utilization method opportunities, adopted in aca-demic work, which ended up generating significant learning for all involved.